Pinched hysteresis with inverse-memristor frequency characteristics in some nonlinear circuit elements. Issue 9 (September 2015) - Fouda, M.E.; Elwakil, A.S.; Radwan, A.G.
Abstract Pinched hysteresis is considered to be a signature of the existence of memristance. However, here we report on a model that exhibits pinched hysteresis yet it may represent a nonlinear inductor or a nonlinear capacitor (both with quadratic nonlinearity) or a derivative-controlled nonlinear resistor/transconductor. Further, the lobe area of the pinched hysteresis loop in these devices has inverse-memristor characteristics; i.e. it is observed to widen rather than decline with increased operating frequency. Experimental results are provided to validate the model.